IDENTIFIKASI POTENSI UNTUK PENGEMBANGAN WISATA ALAM DANAU TAJWID DI KELURAHAN LANGGAM KECAMATAN LANGGAM KABUPATEN PELALAWAN PROVINSI RIAU - Febriani, Ririn; Hadinoto, Hadinoto; Insusanty, Enny (Fakultas Kehutanan Universitas Lancang Kuning, 2019)
This study aims to identify potential in the Lake Tajwid Nature Tourism area in Langgam Village and analyze the Lake Tajwid Nature Tourism potential in Langgam Sub-District, Langgam District, Pelalawan Regency. This research was carried out in Lake Tajwid Nature Tourism in Langgam Sub-District, Langgam District, Pelalawan Regency, this research was conducted for two months from August to September 2018. Lake Tajwid Nature Tourism has quite good potential and many such as the potential of flora and fauna, potential beauty nature, the potential for uniqueness, the potential for cultural attractions such as the annual event that is often held, namely bathing in balimau potang mogan and togak tonggul. The results of the analysis of the potential of ODTWA in Lake Tajwid Nature Tourism area obtained the highest value, namely on the assessment criteria for Land-Based Tourism Objects of 98.97%.